Spring water quality, discharge, and vegetation diversity across land management regimes in UB Forest, Malang, East Java, Indonesia - YULIA AMIRUL FATA; RIFQI RAHMAT HIDAYATULLAH; MASHLAHATUL UMAMI; EREKSO HADIWIJOYO; MOCHAMMAD ROVIQ; CALVIN ILHAM ARVIANO; ROHMAH PUJI LESTARI; MUHAMMAD IKHSANUDIN; MUSLIM BINTANG SAMUDRA; TASYA WULANDARI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fata YA, Hidayatullah RR, Umami M, Hadiwijoyo E, Roviq M, Arviano CI, Lestari RP, Ikhsanudin M, Samudra MB, Wulandari T. 2025. Spring water quality, discharge, and vegetation diversity across land management regimes in UB Forest, Malang, East Java, Indonesia. Biodiversitas 26: 3610-3622. Springs in forested landscapes play a vital role in ensuring the availability of clean water and maintaining essential ecosystem services. This study explored the characteristics of springs in UB Forest, Malang, East Java, Indonesia, focusing on buffer zone conditions in secondary forest and pine plantation forest, water quality, discharge, and vegetation diversity under different land management regimes. The research was conducted across five tributary systems, where water quality was assessed through physical, chemical, and biological parameters, and vegetation diversity was evaluated using the Shannon-Wiener (H') and evenness (E) index. Spring discharge was measured using the volumetric method, with the highest discharge recorded at 0.5 m³/second. Springs in secondary natural forests showed better water quality, more stable discharge, and greater vegetation diversity compared to those in plantation or agroforestry systems. All springs are in riparian zones, within 1 to 30 meters from the nearest river, and the water quality meets drinking, raw water, and irrigation standards. The highest discharge occurred at Dampul 4 (0.5 m³/s), while other springs were below 0.2 m³/s. The buffer zones support 19 plant species, dominated by native vegetation (Ficus gul), with H' values ranging from 0.451 to 1.685 and E from 0.65 to 0.988. All chemical parameters comply with water quality standards (WQS-1 to WQS-4), except for chromium (Cr) and iron (Fe) levels in Petung 21-2 and Codo, which do not meet WQS-1. Positive correlations were found between vegetation diversity and NO2, Fe (moderate), and TDS (strong). These correlations indicate the potential for using vegetation diversity as an indicator of water quality. While the correlation between vegetation diversity and discharge was relatively low (R²: 20%), the findings emphasize the importance of maintaining natural vegetation and establishing protected buffer zones. The natural vegetation-based spring buffer zone protection strategy and long-term monitoring are needed for sustainable forest management efforts and water resource conservation in the tropical forest landscape.